A Carrierless Amplitude Phase (CAP) Modulation Format: Perspective and Prospect in Optical Transmission System - N. M. Ridzuan; M. F. L. Abdullah; M. B. Othman; M. B. Jaafar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The explosive demand of broadband services nowadays requires data communication systems to have intensive capacity which subsequently increases the need for higher data rate as well. Although implementation of multiple wavelengths channels can be used (e.g. 4 × 25.8 Gb/s for 100 Gb/s connection) for such desired system, it usually leads to cost increment issue which is caused by employment of multiple optical components. Therefore, implementation of advanced modulation format using a single wavelength channel has become a preference to increase spectral efficiency by increasing the data rate for a given transmission system bandwidth. Conventional advanced modulation format however, involves a degree of complexity and costly transmission system. Hence, carrierless amplitude phase (CAP) modulation format has emerged as a promising advanced modulation format candidate due to spectral efficiency improvement ability with reduction of optical transceiver complexity and cost. The intriguing properties of CAP modulation format are reviewed as an attractive prospect in optical transmission system applications.